Importance of the Use of Amorphous Gabions in the Face of a Possible Scour on the Continental-Peru Bridge - Atachagua F., Diego E. (2024)
The main objective of this article is to demonstrate the importance and necessity of applying amorphous gabions around the pillars of the continental bridge, to counteract the impact of scour. For the development of the research, the local scour that occurs in the pillars of the Continental Bridge (Madre de Dios, Peru) was calculated, analyzed and compared for return periods of 100 and 500 years; The Hec Ras software was used to perform the hydraulic modeling. The development of the article was accomplished by compiling scour calculation methodologies, such as the Colorado State University (CSU) method. Additionally, it was possible to reach the conclusion that, when working with the CSU method, more real values are obtained in terms of local scour.